Technical Efficiency of Maize Farming Based on Participation Status in The Farmer Corporation Program in Central Lombok Regency - Wiwid Nurul Asmi; Jamhari Jamhari; Jangkung Handoyo Mulyo (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Central Lombok Regency was selected as one of the areas for implementing the farmer corporation program, focusing on maize commodities. The selection of maize aligns with the potential for superior commodities in Central Lombok Regency, which require support through a corporate base approach. This study aims to examine the factors that influence maize farming production, the level of technical efficiency and the factors that are the sources of technical inefficiency of maize farming. The research was conducted in Central Lombok Regency considering that the area is one of the major maize production centers in West Nusa Tenggara. The sample size was determined by quota sampling with 140 farmers. The sampling technique used snowball sampling. The analysis method used the Cobb-Douglas stochastic frontier production function with the maximum likelihood estimation (MLE) approach. The results showed that maize production is influenced by land tenure size, pesticide use, the number of seeds used and the type of seeds planted. The average level of technical efficiency is 0.87. The age factor is known to reduce technical efficiency, while extension services and participant candidate status increase the technical efficiency of maize farming in Central Lombok Regency. Efforts to increase technical efficiency by strengthening farmer groups and expanding access to extension services can be done through increasing the intensity of extension services with relevant, practical and interactive materials so as to attract farmer participation and increase farmer capacity can be achieved.